Dead of winter [large type] - Jones, Stephen Mack (An August Snow novel, 2021)
"Authentico Foods Inc. has been a part of Detroit's Mexicantown for over thirty years, grown from a tiny business to a block-long facility that supplies tortillas to restaurants. Ex-cop and Mexicantown native August Snow has been invited for a business meeting at Authentico. Its owner, Ronaldo Ochoa, is dying, and is being blackmailed into selling the company to an anonymous entity. August wants to know who's threatening his neighbourhood, but his investigation quickly takes a devastating turn. Now August must fight not only for his life, but for the soul of Mexicantown itself"--